Glomerular Disturbances in Preeclampsia: Disruption Between Glomerular Endothelium and Podocyte Symbiosis (2010)
ABSTRACT: Background. Preeclampsia (PE) is the commonest cause of glomerular disease worldwide. Glomerular endotheliosis has been considered as the hallmark of PE, but this lesion is also found in non-proteinuric hypertensive pregnant women. Lately, podocyte alterations have been related to PE. Proposal. Although it has been demonstrated that glomerular endothelium and podocyte alterations are related to PE, we could locate no formal academic discussion that integrates these two phenomena. The demonstration that alterations of the expression of vascular endothelial growth factor (VEGF) by podocytes result in a dramatic endothelial phenotype and that induced production of endothelin-1 by glomerular endothelium provokes podocyte damage could indicate that glomerular lesions in PE result from disruption of the symbiosis between these cells rather than from events occurring independently. We shall try to describe a holistic way of viewing renal disease in PE women, in which the hypertensive emergency is produced by the effects of antiangiogenic proteins on the vascular endothelium, while renal lesion and proteinuria result from the effects of these proteins on both the glomerular endothelium and the podocyte. Conclusions. VEGF deficiency within the glomerulus in women with PE leads to the disruption of podocyte and glomerular endothelium symbiosis. The evidence demonstrating that exogenous VEGF administration in a rat model of PE could alleviate hypertension and proteinuria in these animals are encouraging in view of looking for therapeutic approaches in this direction, nonetheless further evidence should be provided in humans to directly demonstrate that VEGF supplementation could mitigate the symptoms of PE.